Deciphering the role of ttrA and pduA genes for Salmonella enterica serovars in a chicken infection model - Saraiva, M. M.S. [UNESP]; Rodrigues Alves, L. B. [UNESP]; Monte, D. F.M. [UNESP]; Ferreira, T. S. [UNESP]; Benevides, V. P. [UNESP]; Barbosa, F. O. [UNESP]; Freitas Neto, O. C.; Almeida, A. M. [UNESP]; Barrow, P. A.; Berchieri Junior, A. [UNESP] (Taylor & Francis, 2021)
Salmonella enterica serovars use self-induced intestinal inflammation to increase electron acceptor availability and to obtain a growth advantage in the host gut. There is evidence suggesting that the ability of Salmonella to use tetrathionate and 1,2-propanediol provides an advantage in murine infection. Thus, we present here the first study to evaluate both systemic infection and faecal excretion in commercial poultry challenged by Salmonella Enteritidis (SE) and S. Typhimurium (STM) harbouring deletions in ttrA and pduA genes, which are crucial to the metabolism of tetrathionate and 1,2-propanediol, respectively. Mutant strains were excreted at higher rates when compared to the wild-type strains. The highest rates were observed with white egg-layer and brown egg-layer chicks (67.5%), and broiler chicks (56.7%) challenged by SEΔttrAΔpduA, and brown egg-layer chicks (64.8%) challenged by STMΔttrAΔpduA. SEΔttrAΔpduA presented higher bacterial counts in the liver and spleen of the three chicken lineages and caecal contents from the broiler chickens, whereas STMΔttrAΔpduA presented higher counts in the liver and spleen of the broiler and brown-egg chickens for 28 days post-infection (P < 0.05). The ttrA and pduA genes do not appear to be major virulence determinants in faecal excretion or invasiveness for SE and STM in chickens. RESEARCH HIGHLIGHTSttrA and pudA do not impair gut colonization or systemic infection in chicks. Mutant strains were present in higher numbers in broilers than in laying chicks. Mutants of SE and STM showed greater pathogenicity in broiler chicks than layers.
Keywords: 1,2-propanediol; paratyphoid infection; poultry; Salmonella Enteritidis; Salmonella Typhimurium; salmonellosis; tetrathionate